2014
DOI: 10.1111/wre.12099
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to imazamox in Italian weedy rice populations and Clearfield® rice varieties

Abstract: Summary The introduction of imidazolinone‐tolerant rice varieties has made selective Oryza sativa (weedy rice) control possible. We hypothesised that Italian weedy rice populations have variable degrees of susceptibility to imazamox prior to imidazolinone‐tolerant variety introduction. To this end, 149 Italian weedy rice populations collected from fields never before cultivated with imidazolinone‐tolerant varieties were tested in a glasshouse‐based, whole‐plant response screening study. Imazamox was applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…However, several biotypes of weedy rice resistant to ALS-inhibiting herbicides were identified in rice paddy fields three growing seasons after the introduction of IMI-rice to Brazil (Menezes et al 2009;Roso et al 2010b). Similar problems were found in the United States (Shivrain et al 2007), Italy (Andres et al 2014) and Greece (Kaloumenos et al 2013). This problem is challenging the use of IMI-rice because heavy infestations of weedy rice are still present in several fields similarly to the situation that occurred before the introduction of IMI-rice technology.…”
Section: Introductionsupporting
confidence: 71%
See 3 more Smart Citations
“…However, several biotypes of weedy rice resistant to ALS-inhibiting herbicides were identified in rice paddy fields three growing seasons after the introduction of IMI-rice to Brazil (Menezes et al 2009;Roso et al 2010b). Similar problems were found in the United States (Shivrain et al 2007), Italy (Andres et al 2014) and Greece (Kaloumenos et al 2013). This problem is challenging the use of IMI-rice because heavy infestations of weedy rice are still present in several fields similarly to the situation that occurred before the introduction of IMI-rice technology.…”
Section: Introductionsupporting
confidence: 71%
“…; Andres et al. ) should be considered to avoid or minimize the problems associated with this technology. The ALS gene mutations Ala122Thr and Ser653Asn that confer high level of resistance should be used for developing local IMI‐rice cultivars.…”
Section: Conclusion and Future Directionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results from seed bioassay indicate that the continuous exposure of the pre-germinated seeds to the IMI-herbicides has had a significant impact on the seeds growth. The variability of sensitivity to IMI-herbicides among weedy rice populations in petri dish seed bioassay have also been observed in the USA [3,24], Greece [17,25], and Italy [26]. Zhou et al [27] suggested that AHAS inhibition can be achieved at a very low herbicide concentration, similar with the data obtained for those sensitive populations in this experiment (C, S, and MR219), where up to 99% of inhibition was recorded at only 0.25 times recommended concentration.…”
Section: Discussionmentioning
confidence: 94%